Feminism in Nova Scotia: Women's Groups, 1990-2004 - Black, Naomi (Atlantis)

(untitled) (Mount Saint Vincent University, 2006)
This study compares audits of Nova Scotian women's groups in the years 1990 and 2004 to argue that such groups, which sustain feminism, have increased in number although there have been changes in structures and in respect to salient issues.